Following the proceeds of environmental crime : fish, forests and filthy lucre - Rose, Gregory (Abingdon, Oxon : Routledge, 2014)
'Significant quantities of natural resources are illegally harvested and their proceeds laundered in the Asia-Pacific region, fostering corruption and undermining environmental governance. Much illegal exploitation and pollution occurs in countries with poor governance capacities, but much of the sale for profit and money laundering occurs in mature markets with well-developed governance capacities. This book explores ways to address illegal fishing and logging in Asia-Pacific region by the use of cooperative legal measures, particularly anti-money laundering and confiscation of proceeds techniques. Contributors to this volume cover themes including: the nature of transnational environmental crime; patterns in laundering of illicit fish and forest products; networks for distribution of illicit products; weaknesses in current systems for assurance of the legality of products; and international legal cooperation to enforce anti-money laundering laws in relation to illicit products. In considering these topics the book explores how the use of anti-money laundering measures and the seizure of criminal proceeds can be used as innovative policy options to combat transnational fishery and forestry crimes. The book will be of excellent use and interest to scholars and students of environmental law, criminal law, and practitioners in environmental conservation'--
Forests, fish and filthy lucre / Gregory Rose -- Transnational environmental crime in the Asia-Pacific : characteristics and key issues / Lorraine Elliot -- What is environmental crime and how much is happening in Australia? / Samantah Bricknell -- Laundering the proceeds of crime : a global overview / John Broome -- Combating environmental crime with anti money laundering initiatives : indonesian experiences / Yunus Husein -- Regional plan of action to promote responsible fishing practices in the South-East Asia region : cooperative mechanisms / Murray Johns -- Following the proceeds of illegal fishing in the Asia-Pacific : supply chain intervention points / Kate Barclay -- Integrating monitoring control and surveillance and anti-money laundering tools to address illegal fishing in the Philippines and Indonesia / MaryAnn Palma -- Following the proceeds of bluewater crime : case studies from an Australian fishery / Ian Parks -- Monitoring illegal logging at the national level : lessons from Indonesia / Ahmad Dermawan, Krystof Obidzinski and Salwa Amira -- Limitations of aml techniques in controlling illegally logged timber / Anna Sinaga and Sofi Mardiah -- Limitations of AML techniques in controlling imports of illegally logged timber / Duncan Brack -- Governmental coordination to enforce environmental regulatory agencies : Australian experiences / Grant Pink -- Integrating intelligence functions into environmental agencies : australian experiences / James Lehane -- Combating transnational environmental crime : future decisions / Gregory Rose.
Includes bibliographical references and index.
Keywords: Offenses against the environment; Environmental law -- Criminal provisions